TEST ACTIVITIES ANTIOXIDE ETILASETAT FRAMES OF ETHANOL EXTRACTS RED GINGER RANGE (Zingiber officinale var Rubrum) WITH DPPH METHOD (1,1-Diphenyl-2-Picrylhydrazyl) - NI NYOMAN YULIANI; JEFRIN SAMBARA; MARIA ALEXANDRIA MAU (JURNAL INFO KESEHATAN, 2016)
Red Ginger (Zingiber officinale var Rubrum) is one of the most common plant species in the world. Empirically, red ginger is used as a treatment for colds, fever, and pain as well as spices for various recipes of food and beverages. Red ginger contains volatile oil components, non-volatile oils, and starch substances. The volatile oil or volatile oil component gives a distinctive odor component of ginger while the non-volatile oil component or so-called Oleoresin is a complete picture of ginger as a flavor of spiciness. Oleoresin components of gingerol, shogaol, and resin have potential as antioxidants. Antioxidants needed the body to neutralize free radicals in order not to develop and become harmful to the body. This research was conducted to know and measure antioxidant activity of ethyl acetate fraction of red ginger riming ethanol extract (Zingiber officinale var Rubrum) with DPPH method (1,1dipheny-2 picrylhydrazyl) based on IC50 value. The red ginger rhizome was extracted by maceration with 70% ethanol solvent and fractionated using ethyl acetate solvent. The fractionated condensed extract was tested for its antioxidant activity against DPPH radical using UV-Vis spectrophotometer. The results showed that ethyl acetate fraction of ethanol extract of red ginger rhizome Zingiber officinale var. Rubrum) with a concentration of 30, 40, 50, 60 and 70 ppm of very powerful antioxidant with the IC50 value of 41,27 ppm.